POVOS INDÍGENAS E ACESSO À JUSTIÇA: ANÁLISE DO PROCESSO JUDICIAL DA TERRA INDÍGENA LIMÃO VERDE, MATO GROSSO DO SUL - Anderson de Souza Santos (2021)
The present research aims to analyze the judicial process (Appeal Regimental nº 803462/STF) of the Indigenous Territory Limão Verde, of the Terena ethnic group, located in the municipality of Aquidauana in the State of Mato Grosso do Sul, which is being processed at the Supreme Federal Court. Based on the assumption that more and more indigenous peoples and communities have demanded in the judiciary the recognition of their territorial rights, as fundamental rights of solidarity, the analysis Will be guided by the procedutal perspective of access to justice, with the end of tutelage as a paradigm. That previously prevailed under the Indians. Strictly speaking, the procedrual analysis of the institute of the necessary passive litisconsortium ir urgent, which was rejected by the Supreme Court, in the vote of the Reporting Minister Teori Zavasck, maintaining the procedural relationship only between Owner versus Union. Thus, the research seeks to understand how the process of loss of the geographical space of this community, raising this discussion within the debate on the effectiveness of Human Rights in Brazil, describing, in the meantime, the impacto f the state conduct of colonization in western Brazil that resulted in the distribution of land in Mato Grosso do Sul to colonists, to the detrimento f the territories of the original peoples. Another bias is the judicialization of administrative processes for demarcating indigenous territories, as in the case. Taking advantage of the dogmatic legal bias with na emphasis on values, the research Will be interdisciplinary, based on the inductive method, with quanti-qualitative analysis, based on jurisprudence, doctrine, bibliography and documents.